Novel Therapeutic Target(s) for Psoriatic Disease - Thakur, Vishal; Mahajan, Rahul (Frontiers in Medicine, 2022)
Psoriasis and psoriatic arthritis, together known as psoriatic disease, is highly prevalent chronic relapsing inflammatory disease affecting skin, joints or both and is associated with several comorbidities such as cardiovascular, metabolic, psychiatric, renal disease etc. The etiopathogenesis of psoriasis is complex and mainly driven by aberrant immune response owing to the genetic susceptibility and various environmental factors such as trauma, infections and drugs. Recent advances in understanding molecular and cellular pathways have identified tumor necrosis factor-α (TNF-α), interleukin-17 (IL-17), IL-23, IL-22 as major contributors in psoriasis pathogenesis. Advances in the knowledge of pathophysiology, the interaction of autoinflammation and clinical phenotypes have led to the development of highly effective targeted therapeutic agents which include TNF-α, IL-17, IL-23, IL-1 α/β or IL-36 inhibitors or receptor blockers, small molecule drugs like phosphodiesterase-4 inhibitors (apremilast), Janus kinase (JAK) inhibitors, retinoic acid receptor-related orphan receptor γt (RORγt) inhibitors. These novel drugs have promised the potential of improved disease control. In recent years, the transition from biologics to biosimilars especially with TNF-α inhibitors had significant impact on decreasing health care cost and increasing therapeutic options to the patients. However, selection of right treatment for an individual patient still remains challenging. Moreover, interplay between different epigenetic mechanisms such as the DNA methylation, chromatin modifications and noncoding RNA regulation has recently been started to be deciphered. Enzymes inhibitors involved in epigenetic pathways such as DNA methyltransferases and histone deacetylases demonstrated to restore normal epigenetic patterns in clinical settings and have provided the potential as novel therapeutic targets for psoriasis. In this review, we will discuss novel biologic agents and newer therapeutic approaches in treatment of psoriatic disease.